2014
DOI: 10.1007/s00404-014-3394-2
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of corpus luteum haemorrhage in patients on anticoagulation: a report of three cases and review of literature

Abstract: Selected patients with haemorrhage secondary to deranged coagulation can undergo conservative management in consultation with cardiologist and hematologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…So an unnecessary laparotomy could be avoided by keeping the patient under observation. Gupta A. et al [40] reported conservative management of corpus leuteum haemorrhage in patients on anticoagulants.…”
Section: Intra Peritoneal Bleedingmentioning
confidence: 99%
“…So an unnecessary laparotomy could be avoided by keeping the patient under observation. Gupta A. et al [40] reported conservative management of corpus leuteum haemorrhage in patients on anticoagulants.…”
Section: Intra Peritoneal Bleedingmentioning
confidence: 99%
“…The cystic content is mixed with a high attenuation component (45-100 HU) and in some cases it presents a "fluid-fluid haematocrit" level Contrast-enhanced CT may be helpful in excluding other intra-abdominal diseases (e.g., ruptured hepatic adenoma) that can cause hemoperitoneum in the young female patient. [4][5][6][7] A standard protocol is not reported in literature for the management of SH. Historically the treatment of corpus luteum hemorrhage was exclusively surgical, laparotomy or Laparoscopy and suturing, diathermy or wedge resection or even oophorectomy and salpingooophorectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A conservative approach is reported in a few case reports of late. 6,8,11,12,14 In either case the treatment targets at preserving ovarian function as well as at eliminating the source of bleeding. The products that can be used to restore haemostatic parameters and to stop hemorrhage in the case of critical bleeding due to warfarin include Plasma Cell Concentrate (PCC), FFP, and vitamin K. When the patient is haemodynamically stable (systolic BP >90 mmHg) with hemoglobin values that keep being constant over 4-6 hours of monitoring, a conservative approach can be tried if diagnosis of corpus luteal hemorrhage is certain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by suppressing ovulation, CHCs, DMPA, and possibly progestin-only pills can reduce the risk of ovarian hemorrhage. 47 It is important to note that adequate anticoagulant therapy is required to safely use CHCs and progestin-only therapies associated with an increased risk of VTEs. These agents should be discontinued before anticoagulants are stopped.…”
Section: Management Of Anticoagulantassociated Hmb Outpatient Managementmentioning
confidence: 99%